Фильтрация пьезооптических измерений в методе фотоупругости - Тесленко, А. А. (НТУ "ХПИ", 2007)
In this article the aspects of filtering usage of input and output data of photoelasticity method are investigated by simulation methods. The filtering of data is used together with the finite difference method. Restrictions of the filtration method are found out.
Keywords: контроль качества изделий; остаточные напряжения; методы подавления шумов; методы фильтрации